Rennie & roberton's textbook of neonatology expert consult - Rennie, Janet M. (Elsevier, 2012)
Explains how to care for neonates using the very fresh methods. This title represents the neonatal care, providing detailed pathophysiology and clinical chapters on every condition of the neonate and also chapters on the psychosocial aspects of neonatology, such as handling perinatal death and ethical and legal aspects of neonatal care.